The Effect of Using Posse Strategy on Logical Thinking among Second Intermediate Class, Females Students, in Mathematics - et. al., Ghalib Khazaal Mohammed, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research aims to identify the effect of using Posse strategy in logical thinking among second- intermediate class (female students) , in Mathematics. To verify the aims of the research, a null hypothesis was used. (no significant statistical difference was found at the level of (0.05 ) among the average of the scores of experimental group who study under the ordinary method in testing the logical thinking . The current research has been limited to the female students of second intermediate class at intermediate day – time schools, secondary day – time schools, belong to the state directorate of Rasafa / 2 in Baghdad, first academic term of the academic year 2020 – 2021. The researchers s have adopted the experimental approach of the partial control on two groups (experimental and control) of dimensional test. The researchers s have chosen the intermediate school of distinctive students to apply the experiment. Two classes have been chosen randomly to represent the experimental group including (31) students, and other two classes to represent the control group including (30) students. The total number of the students was (61) . The two groups were rewarded in the variables (chronological age calculated in months, previous achievement in mathematics, IQ test and a prior knowledge test), as well as adjusting other variables. The experimental group was taught according to Posse strategy, while the control group was taught according to the ordinary method . The researchers s have studied the two groups by herself . To measure the logical thinking of the female students, the researchers s have prepared a test for this purpose consisting of (30) paragraphs of the multiple choice type with four alternatives. After applying the test and processing the data statistically, using the T-test for two independent samples, the results came out as follows (there is a statistically significant difference at the function level (0.05) between the average scores of the experimental group students who studied according to the Posse strategy and the average scores of the control group students who studied according to the ordinary method of the logical thinking test , and for the benefit of the experimental group ) . In light of the results, several conclusions were obtained. The use of Posse strategy contributes to increasing the effectiveness and excellence of the students and makes them the focus of the educational process, and that the Posse strategy helps the students in the ability to store information, remember it and recall it when needed. The researchers s recommended encouraging mathematics teachers at all school levels to use the posse strategy. Several proposals have been made, including conducting similar studies to know the effectiveness of using posse strategy in other variables; such as concepts acquisition, thinking development, attitudes development, and others tendencies.